TINJAUAN YURIDIS SAHNYA JUAL BELI ATAS SEBIDANG TANAH YANG BELUM DIBAGI WARIS - Karmila Amalia Pesa; Endang Pandamdari (Reformasi Hukum Trisakti, 2022)
Every country's territory or land is a valuable resource. Problem formulation: Under Muara Bulian Court Decision No. 11/Pdt.G/2019/PN, how will legally sell land that has previously been bagged by Waris and how much will the judge's considerations be in compliance with valid legal requirements? A desk-style writing script that is based on second-by-second data is used in the writing process, which is a sort of juridical normative writing. Survey results are objectively assessed and used to support important conclusions with strong reasons. According to the investigation's findings, defendants I and II engaged in a transaction to buy and sell a plot of land, but because this transaction involved the sale of a plot of land, it was not legal transaction; none of the heirs responsible for the inheritance made any requests.